2019
DOI: 10.1098/rsbl.2019.0270
|View full text |Cite
|
Sign up to set email alerts
|

Swimming from coast to coast: a novel fixed-gear swimming gait in fish

Abstract: Bluegill sunfish use intermittent propulsion during volitional swimming. The function of this propulsive mode during routine swimming has not been well quantified. At low speeds, propulsive cycle frequencies and amplitudes were constant, and average speed and power output were controlled by modulating coasting duration. This fixed-gear gait may accommodate muscle level constraints on power production. At higher speeds bluegills switched to a mixed power-modulation strategy, increasing speed and power through i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 25 publications
(28 reference statements)
3
26
0
Order By: Relevance
“…total length of 18.6 ± 1.0 cm. Video sequences (n = 26 total, 4-5 per fish) of bass swimming intermittently were isolated and analysed for swimming speed, propulsive and glide durations, tailbeat frequency, tailbeat amplitude and Strouhal number (St) as described in Gellman et al [20]. Tailbeat frequency and amplitude were determined during the swimming bouts.…”
Section: (A) Swimming Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…total length of 18.6 ± 1.0 cm. Video sequences (n = 26 total, 4-5 per fish) of bass swimming intermittently were isolated and analysed for swimming speed, propulsive and glide durations, tailbeat frequency, tailbeat amplitude and Strouhal number (St) as described in Gellman et al [20]. Tailbeat frequency and amplitude were determined during the swimming bouts.…”
Section: (A) Swimming Studiesmentioning
confidence: 99%
“…Intermittent swimming is a more recently described swimming behaviour in fishes proposed to reduce energy costs at steady, sustainable swimming speeds [16][17][18]. In field studies and laboratory observations, swimming fish will routinely employ a sustainable, aerobic muscle-powered intermittent swimming behaviour in which 2-3 tailbeats are alternated with approximately 1 s glide periods [1,[19][20][21][22]. Importantly, this has been generally observed when fish are swimming volitionally in static water as opposed to induced flows in a laboratory swim tunnel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of the present work is to determine if Atlantic salmon show a thermal acclimation response in the contractile function of their myotomal muscle. Locomotion dominates the energy budgets of animals (Boisclair & Sirois, 1993; Gellman et al, 2019; Irschick & Garland, 2001). Thermal acclimation of the myotomal muscle would therefore be a mechanism to mitigate in part the impact of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, intermittent swimming in fishes is an example of a potentially energy‐saving behaviour at steady, sustainable swimming speeds (Floryan et al ., 2017; Zhao & Dou, 2020). Field and laboratory observations of volitional swimming fish have demonstrated that fish routinely employ intermittent swimming behaviour during aerobically sustainable swimming (Cathcart et al ., 2017; Ellerby et al ., 2018; Gellman et al ., 2019; Han et al ., 2017; Noda et al ., 2016). Modelling suggests that sustained swimming in an intermittent manner ( i.e ., short duration pulpulsive periods of two to three tailbeats interspersed with ~1.0 s glide periods) reduces the energy costs of locomotion (Floryan et al ., 2017; Zhao & Dou, 2020).…”
Section: Introductionmentioning
confidence: 99%